Variação temporal da vazão e da precipitação na bacia do Rio Cuiabá - França, Ildette Soares (2012)
This study evaluates the temporal variation of flows and rainfall in the last 20 years at 8 gauged stations and 13 rainfall at Cuiabá River basin through graphical and statistical analysis, and compares trends temporal variation of rainfall in the last 20 years with scenarios that predicted by the global climate model HadCM3 to this basin. In graphical analysis charts were used temporal, LOWESS curves and correlograms. Statistical analysis was applied Mann-Kendall for identifying trends. In the analysis of climate data was done downscaling statistician with the relationship between the observed rainfall data and data from global climate model HadCM3 for the year 1960-1990 (baseline) and then there was the comparison between the simulated data by future scenarios (A2 and B1) global model (HadCM3) and those observed in historical series for the period 2000-2010, in order to check for concordance between results. The study area has an approximate surface of 41,000 km2 and is located between parallels 14 ° 18 '- 17 ° 00' S and 54 ° meridians 40'-56 ° 55 'W. In the analyzed period it was observed that there are significant trends (p ≤ 0.05) for the streamflow and rainfall. In the flow, there is a predominance of downward trend of average flow rates, minimum and maximum mainly at stations located in the sub-basins Manso, Middle and Lower Cuiabá during the study period, whereas in the sub-basin Alto Cuiabá there is no single trend. Now with regard to rainfall, significant alterations to the study period, however, no single domain for all stations used. The performance of global climate model HadCM3 not shown satisfactory to identify whether the observed trends in precipitation are related to possible climate change.